Bile Duct Adenoma with Oncocytic Features. (28th January 2014) - Johannesen, E. J.; Wu, Zihao; Holly, Jason-Scott
Abstract : Bile duct adenomas are benign bile duct proliferations usually encountered as an incidental finding. Oncocytic bile duct neoplasms are rare and the majority are malignant. A 61-year-old male with a diagnosis of colorectal adenocarcinoma was undergoing surgery when a small white nodule was discovered on the surface of the right lobe of his liver. This lesion was composed of cytologically bland cells arranged in tightly packed glands. These cells were immunopositive for cytokeratin 7, negative for Hep Par 1, contained mucin, and had a Ki67 proliferation index of 8%. The morphology, immunophenotype, presence of mucin, and normal appearing bile ducts, as well as the increased Ki67 proliferation rate, were consistent with a bile duct adenoma with oxyphilic (oncocytic) change. Oncocytic tumors in the liver are rare; the first described in 1992. Only two bile duct adenomas with oncocytic change have been reported and neither of them had reported mucin production or the presence of normal appearing bile ducts within the lesion.